Implementasi Model Project Based Learning dalam Penanaman Karakter Sesuai Nilai-Nilai Pancasila Kelas 5 SDN Bandung 1 - Rista Febi Wulandari; Desty Dwi Rochmania (Universitas Nusantara PGRI Kediri, 2025)
This study aims to implement Pancasila using the Project Based Learning model, the reason researchers use this model is that class teachers more often use learning resources in the form of textbooks and sometimes make their own worksheets that are less interesting for students, this results in students looking less enthusiastic and learning becomes less meaningful. Through this learning model, students